P185 Liverpool healthy lung project: detection of undiagnosed airways disease and significant other findings in a risk stratified lung health check. (December 2018) - Fidoe, D; Hill, S; Gaynor, E; Field, J; Duffy, S; Ledson, M; Grundy, S
Abstract : Introduction: The Liverpool Healthy Lung Project aims to detect early stage lung cancer and other pulmonary disease. At risk individuals are invited to a 'Lung Health Check' followed by risk-stratified CT scans. 'Non-diagnostic' spirometry is performed for patients without known COPD. Abnormal results were verified with diagnostic spirometry. We report here data on detection of airways disease and significant other findings (SOF) in the programme and the consequences to patients and primary care. Methods: Results of diagnostic spirometry for patients who had obstructive 'non-diagnostic' spirometry were analysed. Associated demographic and clinical information was correlated with outcomes of spirometry testing. Rates of SOF on CT scans were calculated. A cohort of 278 SOFs were evaluated in detail. SOFs were categorised as 'Major', 'Minor' and 'clinically insignificant'. Patient pathways were mapped. A GP completed questionnaire on the impact of SOFs from LHLP on primary care was performed. Results: Between April 2016 and November 2017 13 760 people were invited to a Lung Health Check. 5740 participants attended. Spirometry was performed in 2235 people and CT was performed for 1318 people. 560 participants had obstructive 'non-diagnostic' spirometry. 441 completed diagnostic spirometry. Results of diagnostic spirometry: COPD 44%; asthma 10%; normal 35%; restrictive 6%; unclassified 5%. Severity of COPD detected: mild 65%; moderate 32%; severe 3%. 1173 CT scans were reviewed for SOF. 278 (24%) SOFs were detected: 25 (9%) were major; 64 (23%) were minor; 189 (68%) were clinically insignificant. 7.5% of all CTs has a clinically significant SOF. 29/53 questionnaires were returned (15 Major, 14 minor). Median time to clinical review of CT was 5 days. Outcomes are displayed in table 1. Primary care colleagues felt that clinically significant SOFs led to benefit for the patient. Increased workload created by LHLP was not felt to be onerous. Conclusions: LHLP has been successful in detecting high rates of undiagnosed COPD. 65% of COPD detected was mild according to spirometry. The numbers of significant other findings were moderate. The pathway for follow up of these findings within primary care was efficient and did not create a troubling burden of work.